2020
DOI: 10.1101/2020.05.22.111195
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reevaluation of theToxoplasma gondiiandNeospora caninumgenomes reveals misassembly, karyotype differences and chromosomal rearrangements

Abstract: Neospora caninum primarily infects cattle causing abortions with an estimated impact of a billion dollars on worldwide economy, annually. However, the study of its biology has been unheeded by the established paradigm that it is virtually identical to its close relative, the widely studied human pathogen, Toxoplasma gondii. By revisiting the genome sequence, assembly and annotation using third generation sequencing technologies, here we show that the N. caninum genome was originally incorrectly assembled under… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Contigs corresponding to the mitogenome vary widely in size. We found the mitogenome of N. caninum to be distributed in 20 distinct contigs, ranging from 1.4 to 86 kb with a mean of 12 kb in size (Berná et al, 2021). Twenty nine contigs ranging from 1.1 to 39 kb in size, with a median of 8.0 kb, were identified as the mitochondrial genome of T. gondii (Berná et al, 2021).…”
Section: The Mitochondria Of Apicomplexansmentioning
confidence: 92%
See 1 more Smart Citation
“…Contigs corresponding to the mitogenome vary widely in size. We found the mitogenome of N. caninum to be distributed in 20 distinct contigs, ranging from 1.4 to 86 kb with a mean of 12 kb in size (Berná et al, 2021). Twenty nine contigs ranging from 1.1 to 39 kb in size, with a median of 8.0 kb, were identified as the mitochondrial genome of T. gondii (Berná et al, 2021).…”
Section: The Mitochondria Of Apicomplexansmentioning
confidence: 92%
“…However, there are notable exceptions; the mitochondrial genome of coccidians being a beautifully illustrative example. From PacBio and ONT sequencing the number of nuclear chromosomes of both T. gondii and N. caninum was reduced from 14 to 13, and important chromosomal rearrangements between both species were described (Berná et al, 2021;Xia et al, 2021). However, none of the mitochondrial genomes could be completely resolved; neither have been conclusively resolved the level at which the diversity exists nor the mechanisms underlying this diversity.…”
Section: Cox1 Cox3 and Cobmentioning
confidence: 99%
“…Other studies highlighted the need for improved genome assemblies [102] and detailed annotation of the N. caninum genome [103]. It is anticipated that genome assemblies from long and short read sequencing technology will lead to new advances in the application of reverse vaccinology to N. caninum [104] and ultimately efficacious vaccines for that parasite.…”
Section: Discussionmentioning
confidence: 99%
“…Del Cacho, et al [ 34 ] developed a less vigorous method of cell wall breakdown using clorhidric (hydrochloric) acid-ethanol and freeze-thawing; this allowed the visualization of intact pachytene synaptonemal complexes during meiosis by transmission electron microscopy and identification of at least 14 chromosomes in E. tenella [ 29 ]. Interestingly, recent application of third generation Oxford Nanopore genome sequencing to the closely related coccidians Neospora caninum and T. gondii has reduced their karyotypes from 14 to 13 chromosomes [ 35 , 36 ]. Equivalent studies with Eimeria may be similarly informative.…”
Section: Eimeria Genomesmentioning
confidence: 99%
“…Comparison with the T. gondii genome annotation revealed that 93-99% of the core eukaryotic genes were detectable in the tier 1 and 2 Eimeria genomes. As has occurred with Toxoplasma gondii and Neospora caninum [35,36], the application of third generation sequencing technologies can be expected to provide a dramatic improvement in Eimeria genome sequence resources in the near future. na = not applicable (reads aligned against the E. tenella Houghton reference strain, not de novo assembled).…”
Section: Eimeria Genomesmentioning
confidence: 99%